Efikasi Pestisida Nabati Minyak Atsiri Tanaman Tropis terhadap Mortalitas Ulat Bulu Gempinis - ADNYANA, I GEDE SILA; SUMIARTHA , KETUT; SUDIARTA , I PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2012)
ABSTRACT Efficacy of Essential Oils Extracted from Tropical Plants to Hairy Caterpillar Efficacy of some essential oils extracted from tropical plant to hairy caterpillar was conducted in order to find out the method to control population of hairy caterpillar which were increased drastically in 2010 to 2011 in Indonesia. The insect were reported to attack some plants such as: wooden plants; horticulture crops, especially, mango trees and some ornamental plants. Although, these caterpillar have not been found to attack food crops. These insects arising some problems: scared as well as skin etches, etc., especially when these insects entering the communities residence. To control the caterpillar, recently, peoples used chemical insecticide, however the impact of chemicals insecticide is dangerous to human being, livestock, and environmental. Therefore to minimizing those problems, the control methods should be environmental-friendly and safe against human being. One of those methods is utilizing the botanical pesticide which is extracted from tropical plants. Three of topical plants such as: citronellagrass (Cymbopogon nardus), lemongrass (Cymbopogon citratus), neem (Azadirachta indica), were done in this experiment to utilize it as botanical pesticide. The experiment result shown at the concentration 10%, all of the essential oils are effective to kill the caterpillar (90-100%). Therefore the examinations of low concentrations of essential oils were conducted (5, 2, and 1%). The result of 1% concentration of lemongrass was found most effective to kill caterpillar (98%). The examinations for lemongrass under 1% concentration (0.75, 0.50, and 0.25%) were continued. From those examinations, under concentration of 0.50 % the caterpillar was killed 90%, while the concentration of 0.25% was not effective (50%). Keywords: hairy caterpillar, essential oil